The Bolsheviks in Russian society : the revolution and the civil wars - Brovkin, Vladimir N. (New Haven, Conn. : Yale University Press, 1997)
In this book distinguished scholars from East and West draw on recently opened archives to challenge the commonly held view that the Bolsheviks enjoyed widespread support and that their early history was simply a march toward inevitable victory. They show instead that during this period Russian society was at war with itself and with the Bolsheviks. Authors discuss such previously neglected subjects as government policies toward women and toward religious institutions, the protests of workers and peasants, and the anti-Bolshevik movements and parties. Describing not one civil war but several social, political, and military confrontations going on simultaneously, they portray a Russia in turmoil and on outcome that was by no means inevitable.
Introduction: New tasks in the study of the Russian Revolution and the Civil War / Vladimir N. Brovkin -- pt. 1. Paralysis of politics and Bolshevik seizure of power, 1917 -- The Russian Intelligentsia, terrorism, and revolution / Anna Geifman -- The Mensheviks in the fall in 1917: decisions and consequences / O.V. Volobuev -- The left socialist revolutionaries and the Bolshevik uprising / Michael Melancon -- pt. 2. Anti-Bolshevik forces: fragmentation and alienation, 1918-1920 -- The socialists-revolutionaries and the dilemma of civil war / Scott Smith -- The psychology of the White Movement / Leonid Heretz -- Siberian Atamanshchina: warlordism in the Russian Civil War / N.G.O. Pereira -- pt. 3. Popular resistance to Bolshevik dictatorship -- Worker's protest movement against war communism / Sergei Pavliuchenkov -- Peasant rebellions: origin, scope, dynamics, and consequences / Taisia Osipova -- Peasant wars in Tambov Province / Delano DuGarm.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Rossiĭskai͡a kommunisticheskai͡a partii͡a (bolʹshevikov) -- History; Rossiĭskai͡a kommunisticheskai͡a partii͡a (bolʹshevikov); Soviet Union -- History -- Revolution, 1917-1921.; URSS -- Histoire -- 1917-1921 (Révolution); HISTORY; Soviet Union; Bolsjewisme; Rusland; Regions & Countries - Europe; History & Archaeology; Russia & Former Soviet Republics; 1917-1921; History